2018
DOI: 10.1177/1740774518796156
|View full text |Cite
|
Sign up to set email alerts
|

Development of an online resource for recruitment research in clinical trials to organise and map current literature

Abstract: BackgroundRecruiting the target number of participants within the pre-specified time frame agreed with funders remains a common challenge in the completion of a successful clinical trial and addressing this is an important methodological priority. While there is growing research around recruitment, navigating this literature to support an evidence-based approach remains difficult. The Online resource for Recruitment Research in Clinical triAls project aims to create an online searchable database of recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 27 publications
(28 reference statements)
0
35
0
Order By: Relevance
“…The potential barriers to recruitment identified in this study are not unique to trials in breast reconstruction [36,37] and development of strategies to improve recruitment to RCTs is a research priority [38]. Evidence for the effectiveness of existing approaches has been summarised in several recent systematic reviews and has shown to be limited [15,36,37,[39][40][41]. Qualitative research within trials to explore barriers to recruitment, however, is likely to be an effective strategy for allowing recruitment challenges to be understood and overcome [37].…”
Section: Discussionmentioning
confidence: 99%
“…The potential barriers to recruitment identified in this study are not unique to trials in breast reconstruction [36,37] and development of strategies to improve recruitment to RCTs is a research priority [38]. Evidence for the effectiveness of existing approaches has been summarised in several recent systematic reviews and has shown to be limited [15,36,37,[39][40][41]. Qualitative research within trials to explore barriers to recruitment, however, is likely to be an effective strategy for allowing recruitment challenges to be understood and overcome [37].…”
Section: Discussionmentioning
confidence: 99%
“…As the literature on the use of incentives in trials is limited, we drew upon evidence from two other healthcare settings in which incentives are commonly used: pay for performance, and health behaviour change. The ORCCA database was launched in September 2016, bringing together published studies and ‘work in progress’ on recruitment [12]. We updated our search in September 2018 by assessing studies relating to ‘incentives’ in the ORCCA database.…”
Section: Methodsmentioning
confidence: 99%
“…The value of SWATs is increasingly being recognised, with several developments moving to raise their profile and encourage their routine use in RCTs [ 11 ]. These include online research platforms specifically designed to address recruitment and retention challenges within RCTs, such as Trials Forge [ 12 ] and Clinical triAls [ 13 ]. These online resources primarily aim to share knowledge from existing studies and build a platform to collate the findings and inform new hypotheses.…”
Section: Introductionmentioning
confidence: 99%